Effect of gate insulator thickness on device performance of InGaZnO thin-film transistors. (January 2015) - Ding, Xingwei; Zhang, Jianhua; Shi, Weimin; Ding, He; Zhang, Hao; Li, Jun; Jiang, Xueyin; Zhang, Zhilin; Fu, Chaoying
Abstract: Top-contact thin-film transistors (TFTs) are fabricated in this work using atomic layer deposition (ALD) Al2 O3 as the gate insulator and radio frequency sputtering InGaZnO (IGZO) as the channel layer so as to investigate the effect of Al2 O3 thickness on the performance of IGZO-TFTs. The results show that TFT with 100-nm-thick Al2 O3 (100 nm-Al2 O3 -TFT) exhibits the best electrical performance; specifically, field-effect mobility of 5 cm 2 /Vs, threshold voltage of 0.95 V, I on / I off ratio of 1.1×10 7 and sub-threshold swing of 0.3 V/dec. The 100 nm-Al2 O3 -TFT also shows a substantially smaller threshold voltage shift of 1.1 V after a 10 V gate voltage is applied for 1 h, while the values for TFTs with an Al2 O3 thickness of 220 and 280 nm are 1.84 and 2 V, respectively. The best performance of 100 nm-Al2 O3 -TFT can be attributed to the larger capacitance and the smaller amount of total trap centers possessed by a thinner insulator compared to the thicker ones.